Liberatory Pedagogies in the Religious Studies Classroom - Pippin, Tina (Teaching theology and religion, 1998)
The author describes the risks and rewards of her use of liberatory pedagogies in a “Feminist and Womanist Ethics and Spirituality” course. In addition to defining liberation pedagogies and providing a brief bibliography, she includes classroom rules and the projects undertaken that contributed to the character and success of the course.